The Significance of Hylomorphism - De Groot, Jean (Proceedings of the American Catholic Philosophical Association, 2019)
Hylomorphism is a word for Aristotle’s belief that matter and form constitute a unity in natural things. Engaging with the work of Rémi Brague on the cosmos, I propose hylomorphism as central to the contemporary philosophy of nature that Brague seeks. Between the pre-philosophical standpoint and philosophy, there is an intermediate cognitive stage of making initial distinctions that ground philosophical truths. Philosophy of nature is the home of many of these initial distinctions. A key theme introduced in Physics 2.2 is the thinking of things in the way they are capable of existing. Analyses of Physics 2.2. and De Anima 2.3 exhibit the recognition of being as something different from the sheer existing of things. Aristotle points out mistakes in thinking about form and elucidates ontological dependencies. There are implications for the understanding of human disability.